2023
DOI: 10.2478/forj-2023-0003
|View full text |Cite
|
Sign up to set email alerts
|

Difference in the magnitude of power saw vibrations affecting the operator during forest felling

Abstract: This study deals with a question whether the magnitude of vibrations affecting the power saw operator during the tree felling is still the same or not. For this purpose, the tree felling was broken down into several partial operations (pruning of lower tree part; cutting of buttresses; felling; delimbing) at which the values of vibrations were recorded and mutually compared. The vibrations were measured during the felling of 121 trees with the activity being made by one feller with one type of power saw and on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Furthermore, studies performed by Yovi et al (2019) and Goglia et al (2012) have demonstrated that other factors such as chain tension, bar length, fuel quantity in the tank, and operator's experience affect the level of the vibrations transmitted [27,28], which is also influenced by the different operations carried out (e.g., felling, delimbing, pruning, etc.) [29]. The influence of wood species on vibration emission was studied by [15,[30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies performed by Yovi et al (2019) and Goglia et al (2012) have demonstrated that other factors such as chain tension, bar length, fuel quantity in the tank, and operator's experience affect the level of the vibrations transmitted [27,28], which is also influenced by the different operations carried out (e.g., felling, delimbing, pruning, etc.) [29]. The influence of wood species on vibration emission was studied by [15,[30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Chainsaw-handling elements that include cutting defined in this study were simplified with the intention of simpler measurement of vibration magnitude that complies with ISO 5349-1:2001 [9] and ISO 5349-2:2001 [24] standards. In that regard, Staněk et al [30] investigated differences between vibration magnitudes on front and rear handles during cleaning, butt, felling, and delimbing of wet and dry wood and reported a significant difference in 69.23 % of cases. The vibration measurement in this study was conducted on a single tree species (European beech), as it is the most represented species in the Republic of Croatia.…”
Section: Discussionmentioning
confidence: 99%
“…Workload (multiple types) is the most common risk factor with 36 records, followed by vibration and noise with 31 records each, postural load (25), and MSD (11). Again, almost one-third of all records were noted in Brazilian articles (Figure A3) with noise (11), postural load (11), vibration (9), and workload (6) as the most represented. Other countries with five or more records per field include Italy (6) and Poland (5) in the workload field and Romania (5) in the noise field.…”
Section: Article Classificationmentioning
confidence: 99%
“…Risk factors included in forestry ergonomics publications are substantial and their dynamic appearance is observed in this review. Regardless of time period or harvesting systems, "traditional" risk factors like noise [3][4][5][6][7], vibration [8][9][10][11], and workload [12][13][14]…”
Section: Introductionmentioning
confidence: 99%